Renewable Energy in Islamic Countries: A Research Map - Nasution, Abdillah Arif; Shikur, Anwar Adem (SMART Insight, 2023)
This research aims to examine the development of research on the topic of Renewable energy in Islamic countries and research plans that can be carried out based on journals published with that theme. This research uses a qualitative method with a bibliometric analysis approach. The data used are secondary data sourced from the Scopus database, with a total of 46 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of understanding the bibliometric map of research development. The results of the research found in the bibliometric author mapping that the authors who have published the most research on the theme of Renewable energy in Islamic countries are Latip, Normah Abdul; Karim, Rehmat; Marzuki, Azizan; and Aurko, Shafquat Yasar. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can be research pathways related to (1)Islamic finance and renewable energy in Islamic countries, (2)increasing electricity production capacity and renewable energy in Islamic countries, (3)energy consumption and renewable energy in Islamic countries, and (4)economic growth and renewable energy in Islamic countries.